Social, Economic and Political Reformation during British Rule and Its Impact: The Impact of British Rule on Indian Society and Politics (Journal of Advances and Scholarly Researches in Allied Education, 2022)
They put forward some ideas about British ownership, but didn't go too far when they ran into individual problems. British rule had a great impact on Indian culture, economy and culture. A sense of nationhood continued to develop and a sense of nationalism emerged, resulting in a national awakening and anti-British sentiment. The 1857 revolt united and united people of different ethnic, austere and class types against British rule. The revolt stopped the breach of the East India Company, shortly before the changes in British strategy towards the Indian states.